2013
DOI: 10.1902/jop.2012.120075
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Supra‐Alveolar‐Type Defects by a Simplified Papilla Preservation Technique for Access Flap Surgery With or Without Enamel Matrix Proteins

Abstract: The results of this study suggest that combining EMD and SPPF in the treatment of suprabony defects may lead to a greater clinical improvement compared to SPPF alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 43 publications
(105 reference statements)
9
48
4
1
Order By: Relevance
“…found similar results by treating 54 patients with either simplified papilla preservation flap technique (SPPF) + EMD versus SPPF alone (Di Tullio et al. ). After 1 year, the test group showed significantly greater PD reduction, and AL gain compared to the control group (Di Tullio et al.…”
Section: Future Perspectivesmentioning
confidence: 88%
See 1 more Smart Citation
“…found similar results by treating 54 patients with either simplified papilla preservation flap technique (SPPF) + EMD versus SPPF alone (Di Tullio et al. ). After 1 year, the test group showed significantly greater PD reduction, and AL gain compared to the control group (Di Tullio et al.…”
Section: Future Perspectivesmentioning
confidence: 88%
“…After 1 year, the test group showed significantly greater PD reduction, and AL gain compared to the control group (Di Tullio et al. ). Thus, in the light of these two studies and the limited clinical data, it may be suggested to combine either access flap surgery or SPPF with EMD to further improve the regenerative outcomes following periodontal therapy for the treatment of supra‐alveolar‐type defects.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…However, most of the defects in need for periodontal surgery are characterized by horizontal bone loss and/or furcation involvement [33][34][35][36]. In contrast to the external evidence showing the benefits of regenerative measures in vertical bony defects, sufficient evidence showing clinical relevant benefits in furcation and/or horizontal bony defects is still scarce [37,38]. In addition, the prevalence of teeth with vertical bony defects seems to decrease according to a study in a population of dentally aware individuals [39].…”
Section: Discussionmentioning
confidence: 99%
“…Endikasyon: Bu teknik marjinal doku kaybını minimale indirmesi sebebiyle horizontal kemik kayıplarıyla birlikte seyreden problemlerin tedavisinde ve özellikle estetik beklentinin yüksek olduğu bölgelerde tercih edilmektedir. 20 Bu teknik, interdental bölgenin dar olduğu (2 mm veya daha az interdental boşluk) durumlarda önerilmektedir. 21 SPPF geniş anterior/premolar lokalizasyonundaki interdental bölgelerde başarılı iken dar posterior interdental bölgelerdeki başarısı daha sınırlıdır.…”
Section: Basitleştirilmiş Papil Koruyuculu Flep (Bpkf)unclassified